Ecological Diversity of Soil Fauna as Ecosystem Engineers in Small-Holder Cocoa Plantation in South Konawe - Laode Muhammad Harjoni Kilowasid; Tati Suryati Syamsudin; Franciscus Xaverius Susilo; Endah Sulistyawati (UNIVERSITY OF LAMPUNG, 2012)
Taxa diversity within soil fauna functional groups can affected ecosystem functioning such as ecosystem engineers,which influence decomposition and nutrient cycling. The objective of this study is to describe ecological diversityvariation within soil fauna as ecosystem engineers in soil ecosystem of cocoa (Theobroma cacao L.) plantation.Sampling was conducted during one year period from five different ages of plantation. Soil fauna removed from soilcore using hand sorting methods. A total of 39 genera of soil fauna as ecosystem engineers were found during thesestudies. Thirty five genera belong to the group of Formicidae (ants), three genera of Isoptera (termites), and onegenera of Oligochaeta (earthworms). Ecological diversity variation within ecosystem engineers was detected withSimpson indices for dominance and evenness. The highest diversity of ecosystem engineers was in the young ageof plantation. This study reinforces the importance biotic interaction which contributed to the distribution andabundance within soil fauna community as ecosystem engineers in small-holder cocoa plantation.[How to Cite: Kilowasid LMH, TS Syamsudin, FX Susilo and E Sulistyawati. 2012. Ecological Diversity of Soil Fauna as Ecosystem Engineers in Small-Holder Cocoa Plantation in South Konawe. J Trop Soils 17 (2): 173-180. doi: 10.5400/jts.2012.17.2.173] [Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.2.173]